The influence of job stress and job satisfaction towards job performance of secondary cluster school teachers in Kuantan - Kalpana, Ramachandran (2017)
Job performance among teachers have been a topic of interest among many researchers. In this work, the relationships between job stress and job satisfaction towards the job performance of secondary cluster school teachers in Kuantan, Pahang were investigated. The main objectives of this study are to examine the level of performance among the cluster school teachers and to determine the relationships between job stress, job satisfaction and job performance. In assessing the links between those variables, 300 questionnaires were distributed to four cluster schools in Kuantan, Pahang and among them, 226 questionnaires were collected and used in this study. The findings of this study revealed that there are significant relationships between job stress and job satisfaction towards the job performance of the cluster school teachers in Kuantan, Pahang.